"Toward seashells under stress": Bioinspired concepts to design tough layered ceramic composites. Issue 13 (October 2017) - Bermejo, Raúl
Abstract: In this manuscript the potential of building tough, layered ceramic composites with embedded "protective" features has been explored. Novel concepts have been pursued to design ceramics using a non-conventional disposition of "embedded" compressive layers to significantly increase toughness and reduce the scatter in strength. A combination of experiments and modelling has shown the potential of layered architectures in the design of ceramic components with spatially resolved strength and toughness. In addition, texturing of the microstructure in the protective layers has been demonstrated to provide preferential paths for conducting propagating cracks in graceful manner. Recent work has shown that the " flaw tolerance " behaviour of such systems can be enhanced by embedding textured layers holding compressive stresses. Crack arrest and delamination have been observed acting together during the fracture process, which resembles the fracture of nacre. This approach might be further exploited to reduce strength variability and increase toughness in advanced ceramics.